Clues to creation in Genesis - Wiseman, P.J. 1888-1948; Wiseman, Donald John (London, UK Marshall, Morgan and Scott, 1977)
Includes bibliographical references.
Keywords: Creationism; Bible. O.T. Genesis I-II -- criticism, interpretation, etc